Memphis : 1981-1988. - Groninger Museum, Groningen; Stedelijk Museum Amsterdam; Museum voor Sierkunst, Gent; Kestner Museum, Hannover; Badischer Kunstverein, Karlsruhe (Groningen : Groninger Museum, 1989)
Memphis ; Arquitectonica ; Bedin, Martine ; Bley, Thomas ; Branzi, Andrea ; Caturegli, Beppe ; Cibic, Aldo ; Graves, Michael ; Hollein, Hans ; Iosa-Ghini, Massimo ; Kuramata, Shiro ; De Lucchi, Michele ; Mariscal, Javier ; Du Pasquier, Nathalie ; Shire, Peter ; Sottsass, Ettore ; Sowden, George James ; Taylor, Gerard ; Thun, Matteo ; etc.
Memphis 1981-1988, Groninger Museum, Groningen, 26.11.1989 - 14.01.1990 / Stedelijk Museum Amsterdam, 26.01 - 11.03.1990 / Museum voor Sierkunst, Gent, 03 - 05.1990 / Kestner Museum, Hannover, 05 - 07.1990 / Badischer Kunstverein, Karlsruhe, 10 - 11.1990
boek